Analisis Konduktivitas Hidrolik Dengan Metode Bouwer and Rice (1976) - Panji Tegar Aji; Sigit Sutikno; Muhamad Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Land fires are frequent disasters, especially on peatlands. One of the efforts to prevent fire on peatlands is by building canal blocks. The effectiveness of the canal block needs to be analyzed for its effectiveness to find out whether the canal block can prevent peatland fires. Hydraulic conductivity is one of the parameters used to determine the effectiveness of canal block construction. Hydraulic conductivity is the ability of the soil to drain water through it. The purpose of this study is to find out how much the hydraulic conductivity value of peatlands in Lukun Village and to find out whether the canal blocking construction in Lukun Village is effectively built. The results of this study indicate the value of hydraulic conductivity with the Rice and Bower (1976) method is 0.366 m / day - 14.146 m / day. The value of hydraulic conductivity also shows that the construction of canal blocks in Lukun Village is effective in preventing peatland fires.Keywords: Hydraulic Conductivity, Peatland, Rice and Bouwer (1976)